Panca Jiwa Pondok and Contemporary Psychology: A Comparative Review for Contextual Islamic Psychology - Akbar Nur Aziz; Fuad Nashori; Fitriah M. Suud; Halim Purnomo (IJIP : Indonesian Journal of Islamic Psychology, 2025)
One of the most essential values in the Islamic boarding school education system is the concept of the Panca Jiwa Pondok that was developed by Imam Zarkasyi in the Gontor Boarding School. These values serve as a guideline for students' lives and reflect the richness of local wisdom that can be developed within the scientific framework of Islamic Psychology. This article aims to critically examine the relevance of the five values of the Panca Jiwa Pondok to modern psychological theories such as Logotherapy, Self-Determination Theory, Positive Psychology, Attachment Theory, and Existential Psychology. This article analyzes the academic literature from indexed journals in the last ten years through the qualitative literature study method. It relates it to Qur'anic verses and Hadith as the primary normative sources. The study results show a strong wedge of meaning between Islamic values that live in Islamic boarding schools and fundamental concepts in modern psychology. The integration between the local values of Islamic boarding schools, Islamic teachings, and contemporary psychological theories has the potential to strengthen the construction of Islamic Psychology that is more contextual and relevant in answering the educational needs and spiritual mental development of students in the contemporary era. This study emphasizes the urgency of developing Islamic Psychology that is not only normative but also rooted in the social and cultural reality of the ummah.